al Da'wah al islahiyyah fi bilad al Najd 'ala yad al Imam al Mujaddid al Shaykh Muhammad Ibn 'Abdulwahhab wa a'lamiha min ba'dih - 'Abdullah Ibn Muhammad Ibn 'Abdulmuhsin al Mutawwa' (Dar al Tadmuriyyah, 2010)
sgh.2/ws.c.1-2